Assessing the effects of three potential chemical repellents to prevent bird damage to corn seeds and seedlings. Issue 3 (12th April 2012) - Esther, Alexandra; Tilcher, Ralf; Jacob, Jens
Abstract BACKGROUND: Bird damage to seeds and seedlings of maize (Zea mays) and other crops is widespread, especially in organic farming, because no adequate seed protection is available. In this study, the effect of seed treatments with three substances likely to affect bird feeding behaviour (anthraquinone, pulegone and methyl anthranilate) was tested. Their repellent effect was tested in food and seedling choice (treated versus untreated) experiments with feral pigeons (Columba livia f. domestica) in aviaries. Most efficient variants were additionally tested in the field, where wild birds had unlimited access. RESULTS: In aviaries, untreated seeds were clearly preferred over treated seeds by pigeons. The highest feeding deterrence effect occurred with the treatment variants pulegone 1.4 mL kg−1 and methyl anthranilate 0.085 mL kg−1. In contrast, there was no repellent effect if seedlings were offered to the pigeons in aviaries. The same applies to the number of maize seeds and seedlings grown from treated and untreated seeds, which were damaged in the field mainly by pheasants (Phasianus colchicus). CONCLUSION: The study shows that the chemicals failed to repel feeding by birds in Germany. Further studies should concentrate on alternative, systemic effective substances possibly based on plant secondary metabolites to yield a bird repellent usable in organic farming. © 2012 Society of Chemical Industry